Knowledge as property rights under the ratchet effect of innovation - Tan, Teck Yong (2021)
This paper studies how reduced oversight creates an incentive for process innovation. With incomplete contracts, tight monitoring of workers creates a ratchet effect of innovation. Under reduced oversight, a worker accrues private knowledge about his innovation, which serves as a substitute for its inalienable property rights. The resulting asymmetric information generates an information rent for the worker, which feeds back as an innovation incentive ex ante. A weak early production incentive is required to complement it. Innovations are generally underutilized ex post, and mildly successful innovations are not distinguished from failed innovation attempts.